Ibrutinib Plus Rituximab Versus Placebo Plus Rituximab for Waldenström's Macroglobulinemia: Final Analysis From the Randomized Phase III iNNOVATE Study. Issue 1 (1st January 2022) - Buske, Christian; Tedeschi, Alessandra; Trotman, Judith; García-Sanz, Ramón; MacDonald, David; Leblond, Veronique; Mahe, Beatrice; Herbaux, Charles; Matous, Jeffrey V.; Tam, Constantine S.; Heffner, Leonard T.; Varettoni, Marzia; et al.
Abstract : PURPOSE: The double-blind, randomized, placebo-controlled phase III iNNOVATE study showed sustained efficacy of ibrutinib-rituximab in Waldenström's macroglobulinemia (WM). Here, we present the final analysis from iNNOVATE. METHODS: Patients had confirmed symptomatic WM, either previously untreated or previously treated; patients with prior rituximab had at least a minor response to their last rituximab-based regimen. Patients were randomly assigned to once-daily ibrutinib 420 mg plus rituximab or placebo plus rituximab (n = 75 per arm). The primary end point was progression-free survival (PFS). Secondary end points included response rate, time to next treatment, hemoglobin improvement, overall survival, and safety. RESULTS: With a median follow-up of 50 (range, 0.5-63) months, median (95% CI) PFS was not reached (57.7 months to not evaluable) with ibrutinib-rituximab versus 20.3 months (13.0 to 27.6) with placebo-rituximab (hazard ratio, 0.250; P < .0001). PFS benefit was regardless of prior treatment status, MYD88 and CXCR4 mutation status, or key patient characteristics. Higher response rates (partial response or better) were observed with ibrutinib-rituximab (76% v 31% with placebo-rituximab; P < .0001) and were sustained over time. Median time to next treatment was not reached with ibrutinib-rituximab versus 18 months with placebo-rituximab. More patients receiving ibrutinib-rituximab versus placebo-rituximab had sustained hemoglobin improvement (77% v 43%; P < .0001). Median overall survival was not reached in either arm. Ibrutinib-rituximab maintained a manageable safety profile; the prevalence of grade ≥ 3 adverse events of clinical interest generally decreased over time. CONCLUSION: In the final analysis of iNNOVATE with a median follow-up of 50 months, ibrutinib-rituximab showed ongoing superiority across clinical outcomes in patients with WM regardless of MYD88 or CXCR4 mutation status, prior treatment, and key patient characteristics. Abstract :